Contribuições das capacidades dinâmicas no desempenho de PMEs em setores regulamentados da saúde: um estudo múltiplo de casos em Laboratórios de Análises Clínicas - Feijão, Ticiana Mont’Alverne Parente (Universidade do Vale do Rio dos Sinos, 2025)
The perspective of Dynamic Capabilities (DCs) is a prominent theoretical lens in the field of strategic management, given that its focus lies in driving firms toward superior performance. In this discussion scenario, Small and Medium-sized Enterprises (SMEs) are observed as a broad and necessary field for the use of the microfoundations of sensing, seizing, and reconfiguring, since they play a vital role in the global economy by fostering innovation and economic growth while, at the same time, facing restrictions in their operational and financial resources. When inserted in highly regulated sectors, the limitations of SMEs tend to intensify due to the need for compliance with specific standards and legislation, requiring continuous investments that considerably impact firms. The healthcare sector, particularly clinical laboratories, faces an environment characterized by high regulatory complexity and growing demand for quality, safety, and efficiency.This study aims to investigate the contribution of DCs to the performance of SMEs operating in highly regulated sectors, taking into account the constant evolution of the business environment and the requirements of adaptation to technological changes and strict regulations. Through qualitative research, using a multiple case study approach, the study sought to deepen the findings of the microfoundations that led to performance in laboratories by operationalizing the final categories identified. The results show that regulation, often perceived as an obstacle, is reinterpreted by the laboratories investigated as a strategic lever. Sensing presented the greatest contribution of the study, since from the perception of opportunities by managers, strategies could be designed, and resources reconfigured in the pursuit of performance in an agile and assertive way, favoring organizational longevity. Seizing and reconfiguring, although contributing to performance, are intertwined, making it difficult to identify when the laboratory designs the strategy and when it orchestrates, acquires, measures, or combines resources to implement it, which suggests the absence of specialized departments in SMEs.Therefore, the potential of this study revolves around the responsiveness that SMEs demonstrate through the use of DCs, bringing legitimacy to the role of accreditation and regulatory bodies in the sustainable development of firms through quality. This research has the capacity to share scientific knowledge both with the management sciences and with the health sciences literature, by means of the scientific evidence generated, since the final categories of the microfoundations can provide important tools for operationalization in contemporary laboratory management.
Keywords: Capacidades dinâmicas; Pequenas e Médias Empresas; Setor de saúde; Desempenho organizacional; Dynamic capabilities; Small and Medium-sized Enterprises; Healthcare sector; Organizational performance; ACCNPQ::Ciências Sociais Aplicadas::Administração